Numerical modelling of a solar salt pan for improved salt production at Lake Katwe, Uganda - Hillary Kasedde; Aidah Namagambe; Joseph Ddumba Lwanyaga; John Baptist Kirabira; Denis Okumu (Case Studies in Thermal Engineering, 2023)
The solar salt pans at Lake Katwe are set up haphazardly without any scientific guidelines which compromises the annual throughput from the solar salt works. To improve on the design of the salt pans, the heat transfer dynamics of the salt pan have been numerically and experimentally studied in this study. A representative salt pan located at the shores of the lake Katwe with a surface area of 62 m2 and a depth of 0.2 m was used in this study. The numerical model was implemented in the OpenFOAM software where a 3D heat transfer salt pan model was studied using the Finite Volume Method under Lake Katwe climatic conditions. The model was governed by continuity, salt concentration, momentum, energy equations and the Boussinesq approximation. A field experiment that determined the temperature variation with depth was carried out. The correctness of the model results was verified against experimental data. The numerical simulation model revealed a salt pan brine temperature increase with time and the salt concentration significantly remained constant with time. The salt pan brine temperature increased from 303 K to 319.5 K after 5 h of the simulation time. The model and the experimental salt concentration and temperature profiles were found to be in a good agreement. The sensitivity analysis on the effect of the salt pan depth on brine temperature was studied. It was revealed that the shallower the salt pan, the higher the rate of heat gain. This study revealed that an optimum salt pan depth to yield a higher salt quantity under Lake Katwe climatic conditions was at 0.1 m.